A SULPHUR HEXAFLUOROIDE GAS LEAKAGE DETECTION SYSTEM USING WIRELESS SENSOR NETWORKS - Šoštarić, Damir; Horvat, Goran; Nikolovski, Srete (Journal of Energy Technology, 2024)
Most high-voltage (HV) transformer stations currently use sulphur hexafluoride (SF 6) gas as a dielectric to prevent arcing in circuit breakers. The excellent dielectric properties of SF 6 allow HV equipment to be constructed in only 10–20% of the volume/space of air insulation. Reductions of SF 6 gas density in circuit breakers cause failures in providing the required interrupter insulating properties and can lead to operational inefficiencies and safety hazards. SF 6 has a global warming potential 23,900 times that of CO 2; therefore, any leakages must be strictly monitored. The most fundamental measure against the uncontrolled emission of the SF 6 gas into the atmosphere is the constant monitoring and detection of its leakage in energy facilities. The methods for the SF 6 leakage detection should be extremely precise, while simultaneously having acceptable implementation costs. This paper presents a solution for an SF 6 gas monitoring system using Wireless Sensor Network (WSN) nodes. These nodes use multi-hop networking to transmit data to a base station connected to the other stations and the internet through a secure VPN (Virtual Private Network) connection. Using wireless sensing systems also significantly decreases installation time and reduces costs of materials and labour.